EFEKTIVITAS LAYANAN KONSELING KELOMPOK PENDEKATAN BEHAVIOR DENGAN TEKNIK KONTRAK PERILAKU UNTUK MEREDUKSI MONEY WASTING SISWA KELAS VIII SMP ASY-SYIFA BOARDING SCHOOL SUKOHARJO TAHUN PELAJARAN 2025/2026 - Siti Nur; Jawandi, Ahmad; Adi Putro, Eko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The purpose of this study was to determine the effectiveness of group counseling services with a behavior approach using behavioral contract techniques in reducing money wasting behavior at the eighth grade students of Asy-Syifa Boarding School Sukoharjo in the academic year 2025/2026. Money wasting is the habit of spending money uncontrollably which has a negative impact on students' financial management. The research method used was an experiment with a one-group pretest-posttest design. The sample consisted of 6 students who exhibited money wasting behavior, selected through purposive sampling. Group counseling services were provided over several sessions focusing on creating behavioral contracts as an effort for self-control. With a significance value of 0.027 < 0.05, Ho was rejected and Ha was accepted. The results of data analysis using statistical tests showed a significant decrease in money wasting behavior after the group counseling intervention. Thus, it can be concluded that there is a difference in the mean between before and after the implementation of group counseling with behavioral contract techniques, which is effective in reducing money wasting behavior in grade VIII students of Asy-Syifa Boarding School Sukoharjo. These findings indicate that the behavior approach with behavioral contract techniques is effective in helping students manage their spending behavior more wisely. The implications of this research are expected to serve as an alternative strategy in school counseling services to increase students' awareness and control of financial behavior.